2017
DOI: 10.1017/9781316218990
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Chinese Philosophy

Abstract: This comprehensive introduction to early Chinese philosophy covers a range of philosophical traditions which arose during the Spring and Autumn (722-476 BCE) and Warring States (475-221 BCE) periods in China, including Confucianism, Mohism, Daoism and Legalism. It considers concepts, themes and argumentative methods of early Chinese philosophy and follows the development of some ideas in subsequent periods, including the introduction of Buddhism into China. The book examines key issues and debates in early Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 178 publications
0
26
1
Order By: Relevance
“…In the Western Han dynasty (202 BCE to 8 AD), Yijing was officially legitimised as one of the five Confucian classics, and later became a textbook for ancient China's imperial examination system in the Tang dynasty (618-907 AD). Since then, the Yin-Yang harmony philosophy as the central theme of Yijing has had significant political influence, constituting the basis of social governance and order in people's daily lives, as well as underpinning the highest form of virtue in terms of being a gentleman (Lai, 2008;Ji et al, 2010;Zhang et al, 2016;Liu, 2017).…”
Section: Historical Basis Of Yin-yang Harmony (Taiji)mentioning
confidence: 99%
“…In the Western Han dynasty (202 BCE to 8 AD), Yijing was officially legitimised as one of the five Confucian classics, and later became a textbook for ancient China's imperial examination system in the Tang dynasty (618-907 AD). Since then, the Yin-Yang harmony philosophy as the central theme of Yijing has had significant political influence, constituting the basis of social governance and order in people's daily lives, as well as underpinning the highest form of virtue in terms of being a gentleman (Lai, 2008;Ji et al, 2010;Zhang et al, 2016;Liu, 2017).…”
Section: Historical Basis Of Yin-yang Harmony (Taiji)mentioning
confidence: 99%
“…In addition, Confucius encouraged people to learn from the past and study classic literature, because he believed that learning helps to cultivate one's virtues. He suggested that everyone should be devoted to self-cultivation, learning and practicing ren to promote harmony in the society (Lai 2008).…”
Section: The Confucian Legacy In Taiwanese Societymentioning
confidence: 99%
“…In ancient China, people adopted their society's exemplary norms to have an orderly and peaceful society. The work of traditional, renowned Chinese philosophers and educators such as Lao Zi, Confucius, Mencius, Mo Zi, Zhuang Zi, Xun Zi, and Zhu Xi became schools of thought that continue to typify Chinese traditional values, guide the Chinese on their journeys through life, and serve to preserve social harmony (Bakken, 2000;Di, 2016: 41;Lai, 2017). Their collective thought forms the foundation of Chinese exemplary norms, which are passed down through the generations and find embodiment in the people influenced by these idas (Di, 2016: 41;Wang, 2006;Wu, 2016).…”
Section: The Exemplary Values In Traditional Chinese Societymentioning
confidence: 99%